The anti-cancer effect of the pentane fraction of Daucus carota oil extract is mediated through cell cycle arrest and an increase in apoptosis - Mroueh, MA (2013)
Daucus carota L. ssp. carota (Apiacea) is used in traditional medicine in Lebanon and in different regions throughout the world. Previous studies from our laboratory demonstrated the in vitro anticancer activities of Daucus carota oil extract (DCOE) on colon and breast human cancer cell lines. In the current study, we aimed at fractionating the Daucus carota oil extract (DCOE) and analyzing the in vitro anticancer activities of the obtained fractions. The pentane fraction (PF) proved to have a highly cytotoxic effect on cancer cells. Cell cycle analysis showed that the cells treated with 25 mg/ml of the pentane fraction completely stopped cycling and had a substantial decrease in the number of cells in G2. PI/Annexin staining also showed an increase in apoptosis in cells treated with PF. Western blot analysis of several apoptotic proteins also proved a direct activation of PF of the apoptotic pathway in cancer cells. The fact that the drug affected both apoptosis and the cell cycle suggested that it is exerting its effect on an effective pathway such as the PI3K pathway or the MAPK pathway. We treated the cells with PF and performed western blots looking at p-Akt and p-ERK. We indeed determined that the PF treatment led to a decrease in p-ERK as compared to total ERK levels, whereas the level of phosphorylated Akt was not affected. This showed that the anti-cancer effect of the PF fraction of wild carrot is due to its inhibition of the ERK pathway which leads to cell cycle arrest and an increase in apoptosis in the tested cancer cells.